Numerical modeling of actual evapotranspiration of a coffee crop - Cesanelli, Andrés (2011)
The evapotranspiration estimation has great importance to crop productivity and agricultural water management. In this study, evapotranspiration is analyzed in a coffee (Coffea arabica L.) crop located in Piracicaba, state of São Paulo (Brazil) using a numerical method based on the simulation of both water flow and crop activity in the unsaturated zone of the soil. Actual evapotranspiration is estimated from potential evapotranspiration using water stress functions, meteorological data, soil hydraulic parameters, crop coefficients and leaf area index values. Crop transpiration and soil evaporation are individually quantified improving the analysis of the evapotranspiration process. The numerical procedure can predict periods of crop water stress and becomes an attractive tool to analyze the effect of non-standard conditions on coffee crops and to design efficient irrigation schedules. Simulated evapotranspiration values are in good agreement with experimental values determined in the study site.